The relationship between generation Y's characteristics and acceptance of social network as job search engine - Logeswran, Ramasamy (2013)
Acceptance of social network as job search engine is based on the determinations of Generation Y’s characteristics. The aim of this study is to determine the relationship between Generation Y’s characteristics of technology savvy, diverse, impatient and ambitious and acceptance of social network as job search engine. This cross-sectional study was conducted among 344 final year undergraduates from University of Malaya (UM). Random sampling technique was the sampling technique used in this study. Four adapted questionnaires were used to measure the Generation Y’s characteristics of technology savvy, diverse, impatient and ambitious and acceptance level of social network as job search engine. Regression analysis was applied to test the hypotheses. The result showed that technology savvy, diverse and impatient are the influencing characteristics of the respondents to accept social network as their job search engine. Technology savvy has been found as the strongest characteristic in influencing the acceptance level of social network as job search engine. Finally, discussion, limitation of the study, suggestion and conclusion also were discussed in order to create platform for future researcher to enhance this study